GROWING POTATO SPROUTS UNDER LIGHT EMITTING DIODES - M, Khalil M; El Aal, AMH Abd (Potato Journal, 2017)
Lighting emitting diodes (LEDs) offer a good tool for use in agricultural applications. Potato sprouts are used for varieties distinctness, uniformity and stability (DUS) tests. The current study investigated the effect of growing potato light sprouts under different LED light qualities and the possibility of using LEDs as light source for growing potato sprouts for DUS tests. The results revealed that white LEDs could be a good source of lighting for growing light sprouts for DUS tests. Red LEDs produced tall thin sprouts with the lowest dry weight. White fluorescent produced the highest anthocyanin content. Varietal differences observed between the tested varieties in length, width, fresh weight, dry weight and anthocyanin content.